Policy change - review of classification, measurement and factors - Šinko, Milan (Teorija in praksa, 2016)
Judging by bibliometric indicators there is an increasing interest in the topic of policy change and its explanation among policy analysts. However, there is no theoretical consensus on how to define the concept of policy change, or which theoretical models best explain its occurrences. On one hand, there is a variety of conceptualisations of policy change, and on the other, a variety of approaches, theories and modes that seek to elucidate the process of change. Based on literature review, the paper compiles a repository of contemporary theories and classifications in the area of policy change, taking into account elements such as the degree of innovation, the dynamic and depth of change and similar. The second part offers a review of policy change models, taking Giessen's classification of nine policy change factors as its general framework. The paper concludes with a discussion on the fast developing field of policy change analysis, which requires careful consideration when selecting a specific approach to analyse the policy change aspects of the policy process.
Keywords: analiza; Changes; Javna politika; Measurement; Merjenje; nastanek; politične spremembe; Public policy; Spremembe; Transition; Tranzicija